From Production to Consumption: Inflationary Challenges and Sectoral Responses in Modern Economy (Journal of Informatics Education and Research, 2025)
Inflation has re-emerged as one of the most pressing challenges for global economies, reshaping the dynamics of production, consumption, and governance. This study examines the multifaceted nature of inflation by exploring its impact on pricing strategies, sectoral reallocation, control mechanisms, and sectoral responses. Drawing on a wide range of scholarly literature, the research demonstrates that inflation is not merely an aggregate macroeconomic phenomenon but is deeply rooted in sector-specific dynamics and structural transformations. The analysis reveals that businesses adapt their pricing strategies in multiple ways, including price increases, shrinkflation, and dynamic pricing, in order to safeguard profit margins amid rising costs. However, price stickiness within supply chains creates persistent inflationary pressures, prolonging its effects across the economy. The study also highlights the role of sectoral reallocation, particularly during the COVID-19 pandemic, where demand shifted sharply from services to goods. This imbalance between demand surges and supply rigidities intensified inflation and exposed structural vulnerabilities in global supply chains. In terms of policy, the research underscores the limitations of relying exclusively on monetary tightening to control inflation, particularly when inflation is driven by supply-side shocks or geopolitical disruptions. Instead, effective inflation management requires a coordinated framework that integrates monetary, fiscal, and social policies. This includes targeted subsidies, welfare measures, and regulatory oversight of corporate pricing practices. Such multidimensional approaches are vital for balancing economic stabilization with equity and welfare. Furthermore, the study analyzes sectoral responses across production, energy, retail, logistics, and households. While production and manufacturing industries pursue efficiency and cost-cutting strategies, the energy sector faces challenges of volatility and reliance on subsidies. Retailers increasingly deploy shrinkflation and loyalty schemes, while logistics industries invest in diversification and digital technologies. Households, meanwhile, adjust consumption patterns by prioritizing essentials and shifting toward cheaper alternatives. These responses reveal both adaptive resilience and the socioeconomic costs of inflation. Overall, the findings emphasize that inflation must be understood as a structural, sectoral, and social phenomenon rather than merely a monetary one. By integrating insights from production to consumption, this study contributes to a deeper understanding of inflationary challenges and offers policy-relevant insights for building resilience in modern economies.